A proof of Kirchhoff’s first law for hyperbolic conservation laws on networks - Bayen, Alexandre M.; Keimer, Alexander; Müller, Nils (Networks and Heterogeneous Media, 2023)
In dynamical systems on networks, Kirchhoff’s first law describes the local conservation of a quantity across edges. Predominantly, Kirchhoff’s first law has been conceived as a phenomenological law of continuum physics. We establish its algebraic form as a property that is inherited from fundamental axioms of a network’s geometry, instead of a law observed in physical nature. To this end, we extend calculus to networks, modeled as abstract metric spaces, and derive Kirchhoff’s first law for hyperbolic conservation laws. In particular, our results show that hyperbolic conservation laws on networks can be stated without explicit Kirchhoff-type boundary conditions.
CRIS-Team Scopus Importer:2024-12-16
Keywords: analysis of pdes; conservation laws; mathematical modeling; networks